A MOTOR VEHICLE AND A BRAKING SYSTEM THEREOF - MOHAN, Shanmugam; VENKATA MANGA RAJU, Karnam; GOWRISANKAR, Shanmugasundaram (2023)
The present subject matter provides a motor vehicle comprising one or more wheels. A wheel-brake system (102) corresponding to each of said one or more wheels is provided. The wheel-brake system (102) includes a cam lever (118) and one or more brake cables (112, 116) are connected thereto. Each of one or more protective cover members (202) is provided on and covering at least a portion of corresponding elastic return member (132, 134). The protective cover member (202, 204) comprises a holding portion (222, 242) having an axial length being greater than a maximum traversal distance (Y11, Y21) of corresponding brake cable (112, 116) about the cam lever (118). The protective cover members (202, 204) have a folding portion (224, 244), which maintain desired clearance even in hard braking condition of any of the brakes.